COMPARATIVE DEMOGRAPHIC PARAMETERS OF FALL ARMYWORM (SPODOPTERA FRUGIPERDA) ON FIVE HOST PLANTS - Naeem Ahmad; Muhammad Ishtiaq; Dr. Muhammad Rafiq Shahid; Farrukh Baig; Rana Mubashar Hassan (Journal of Animal and Plant Sciences, 2025)
The fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) is an invasive insect pest that threatens a wide range of host plants throughout the world. In Pakistan, it was reported, for the first time in maize crop during 2019-20 from samples received from Sindh province. This study explores the biology and fecundity of S. frugiperda across five different host plants i.e. maize (Zea mays), sorghum (Sorghum bicolor), cotton (Gossypium hirsutum), spinach (Spinacia oleracea) and cauliflower (Brassica oleracea). Results revealed that maize was the most suitable host of S. frugiperda, with shortest larval developmental time (21 days), maximum survival rate (95%) and highest fecundity (1573 eggs/female). Sorghum ranked second, followed by cotton, spinach, and cauliflower as the least preferred host. The maximum larval developmental time was observed on cotton (28 days), whereas female fecundity was lowest on cauliflower (1396 eggs/female). All lifetable parameters were found highest on maize plant. It was concluded that S. frugiperda demonstrated maximum preference for maize compared to the other tested host plants. However, order of preference of host plants by S. frugiperda was as maize > sorghum > cotton > spinach > cauliflower. These findings underscore the role of maize in supporting population growth of S. frugiperda, and also suggest alternative host crops where targeted pest management strategies can be focused.
Keywords: host preference; life table; survival rate; reproductive rate; life expectancy